Digital Accounting for MSMEs: A Bibliometric Analysis of Research Themes (2005–2026) - Loso Judijanto; Mos Indrawati (West Science Accounting and Finance, 2026)
This study aims to map the intellectual structure, thematic evolution, and emerging research trends in digital accounting for Micro, Small, and Medium-sized Enterprises (MSMEs) through a bibliometric analysis of publications from 2005 to 2026. Data were collected from the Scopus database using relevant keywords related to digital accounting, accounting information systems, cloud accounting, and MSMEs. A total of selected publications were analyzed using VOSviewer to examine keyword co-occurrence, thematic clusters, and temporal developments. The findings reveal that the research field has evolved from a focus on basic adoption factors such as financial literacy and accounting information systems toward more advanced themes including digital transformation, decision-making, and technological innovations such as blockchain and digitization. The results also indicate that MSMEs remain the central focus of the literature, with increasing attention to how digital accounting enhances business performance and strategic capabilities. Despite the growing body of research, emerging themes related to advanced technologies and data-driven decision-making remain underexplored, highlighting opportunities for future studies. This study contributes by providing a comprehensive overview of the development of digital accounting research in the MSME context and offers insights for researchers, practitioners, and policymakers in supporting digital transformation and sustainable growth of MSMEs.